Trichophyton mentagrophytes genotype VII, an emerging infection: a Systematic Review - Cofone, Luigi; Paglione, Lorenzo; Grassi, Fabiano; Patania, Federica; Pindinello, Ivano; Quarantiello, Antonia; Sabato, Marise (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. In the past few years there has been a dramatic change in the prevalence of the genotype VII of the Trichophyton mentagrophytes. Trichophyton mentagrophytes is a dermatophyte fungus commonly found in wild, terrestrial and burrowing animals such as rabbits, that has now adapted to an anthropophilic environment and is responsible of an emerging zoonosis. Study design. A thorough background research and a systematic review have been done to show the effect of this emerging dermatophytic infection on humans. Methods. Three electronic databases were searched for eligible studies: PubMed, Scopus and Web of Science. All the articles found were then screened, first, by title and abstract and, then, by full text. A quality assessment was done using the Newcastle–Ottawa Quality Assessment Scale (NOS). Results. 28 articles were found. 4 of which were included in this review. These articles were produced in France, Switzerland, the USA and Germany. They showed interesting clinical evidence regarding how this inter-human multidrug resistant mycosis could easily become an epidemic sexually transmitted infection. Conclusions This systematic review emphasizes how the spread of this pathogen, genotype VII, in humans must not be underestimated. Consequently, in order to facilitate early intervention and, thus, avoid a multi resistant epidemic growth of this infection, new diagnostic measures are required.